Efektivitas Pemberian Pelet Berbahan Limbah Ikan Terhadap Pertumbuhan Ikan Lele (Clarias garipienus) - Ahmad - Fahrizal; Ratna Ratna (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2019)
The purpose of this study is to determine the effectiveness of the provision of pellets based on fish waste from TPI Jembatan Puri, Sorong City on the growth of catfish (Clarias sp.). The method used in this study is an experimental method including a test of feed to which includes 5 treatments and 3 replications. Fish meal making and fish waste material from PPI. The results of this study were preceded by previous studies that developed feed made from fisheries waste into pellets that were tested biologically to catfish, beginning with weighing the fish first as preliminary data for fish growth and then also measuring water quality as a factor affecting fish growth in a way live. The results of the study showed that the highest growth rate, the highest was obtained in treatment A (0.73% / day), for the highest feed efficiency in Treatment A, 1.49% for the best FCR, namely Treatment B, 0.28, and The best SR in treatment D was 93%. The conclusion from the results of the study showed that the growth of catfish in the nursery stage was quite effective for the growth of catfish by using fish-based feed even though the results obtained were not significantly affected (P <0.05) for each treatment using different feeds between commercial feed (pellets) and feed made from fish waste.